Jane Grigson: The Enjoyment of Food - The Best of Jane Grigson (compiled by Roy Fullick) - Davidson, Alan E (Petits Propos Culinaires, 1992)
Jane Grigson: The Enjoyment of Food - The Best of Jane Grigson (compiled by Roy Fullick): Michael Joseph, London, 1992: 480 pp, brief introduction by Elizabeth David, index, £18.99.